Control of special physical training for qualified female volleyball players of different games roles - Hammoodi, M. F. K.; Shlonska, O.; Borysova, O.; Imas, Y.; Gamalii, V.; Nagorna, V.; Yakusheva Y. (Acta Kinesiologica, 2022)
Modern competitive activity in volleyball makes high demands on the fitness of athletes, where the leading role belongs to technical-tactical and special physical. Control and interconnection of technical-tactical and special physical fitness will ensure to provide the effectiveness of the training system for qualified female volleyball players. The aim of the research is to analyze the manifestation of special physical qualities of qualified female volleyball players of various playing roles and their interconnection with the effectiveness of technical and tactical actions. The study has involved 48 qualified volleyball players (including 6 masters of sports of Ukraine, 20 candidates for masters of sports of Ukraine, 22 female athletes of the first sports category). Close correlations were obtained between the absolute and relative indicators of the use of technical and tactical actions with the special preparedness of qualified female volleyball players: for binders - the results of the test of flexion and extension of the arms in the lying position closely correlates (r = 0.78 and 0.84) with the efficiency of the serve; for players of the second temp of attack rate - the results of the shuttle run test (9-3-3-9 m) closely correlate (from r = 0.77 to 0.88) with the serve; for the players of the first temp of attack rate, the performance of the test of raising the trunk in the prone position closely correlates (r = 0.70 and 0.78) with the effectiveness of the ball pass; libero - the highest correlational connections (r = 0.92 and 0.96) are observed when performing the shuttle run test (9-3-3-9 m) and the effectiveness of protective actions. On the basis of the obtained significant correlation coefficients, linear regression models of the relationship between the effectiveness of the application of technical and tactical actions and the results of pedagogical testing were constructed.